2019
DOI: 10.3389/fphys.2019.00322
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Scarring in Craniofacial Wound Repair

Abstract: Fibrosis is intimately linked to wound healing and is one of the largest causes of wound-related morbidity. While scar formation is the normal and inevitable outcome of adult mammalian cutaneous wound healing, scarring varies widely between different anatomical sites. The spectrum of craniofacial wound healing spans a particularly diverse range of outcomes. While most craniofacial wounds heal by scarring, which can be functionally and aesthetically devastating, healing of the oral mucosa represents a rare exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 120 publications
1
71
1
3
Order By: Relevance
“…For example, as discussed earlier, recent studies have identified distinct profibrotic and proregenerative fibroblast subtypes within different tissues, highlighting fibroblasts’ functional diversity. 17 These discoveries have the potential to inform novel therapeutic directions; for instance, basic science discoveries of mechanical signaling pathways driving profibrotic fibroblast behavior have been translated into therapies to reduce scarring by targeting wound tension. 13 15 Additional insights into fibroblast heterogeneity, signaling, and lineage hierarchies may allow researchers to target specific fibroblast populations and cell signaling pathways to prevent fibrosis in the dermis and other tissues, with the potential to expand therapeutic strategies available to plastic and reconstructive surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as discussed earlier, recent studies have identified distinct profibrotic and proregenerative fibroblast subtypes within different tissues, highlighting fibroblasts’ functional diversity. 17 These discoveries have the potential to inform novel therapeutic directions; for instance, basic science discoveries of mechanical signaling pathways driving profibrotic fibroblast behavior have been translated into therapies to reduce scarring by targeting wound tension. 13 15 Additional insights into fibroblast heterogeneity, signaling, and lineage hierarchies may allow researchers to target specific fibroblast populations and cell signaling pathways to prevent fibrosis in the dermis and other tissues, with the potential to expand therapeutic strategies available to plastic and reconstructive surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have contrasted fibroblasts from the dermis (which heals via scarring) and oral mucosa (which is minimally scarring). 17 In their 2015 article, Rinkevich et al 10 demonstrated via reciprocal fibroblast transplantation that the fibroblasts responsible for tissue repair in the mouse oral mucosa (defined by Wnt1 expression) are intrinsically nonfibrotic, whereas En1 -positive fibroblasts from the dorsal dermis are intrinsically scar producing. This finding suggested that cell-intrinsic fibroblast differences may contribute to distinct healing outcomes between these sites.…”
Section: Fibroblasts In Wound Healingmentioning
confidence: 99%
“…This similarity in the tissue architecture permits a direct comparison of healing in the skin and mucosa. Mucosal wounds, including those in the gingiva of the oral cavity and lining mucosa of the vagina, heal remarkably quickly and with reduced scar formation as compared to similar size skin wounds [ 44 ]. Many basic elements of repair are different in mucosal wounds, including reduced inflammation, accelerated re-epithelialization, and refined angiogenesis, reducing the need for capillary remodeling.…”
Section: Macrophage Function In Specific Wound Typesmentioning
confidence: 99%
“…Haemostasis is triggered by damage to the vascular endothelium, which reveals the sub-endothelial extracellular matrix (ECM) [25]. Exposure of matrix components facilitates platelet adhesion to ECM resulting in platelet activation and initiation of the haemostatic cascade [26]. Activated platelets contain abundant chemokines and cytokines at concentrations far greater than the plasma concentration [27].…”
Section: Haemostasismentioning
confidence: 99%